Metodologia experimental para a maximização do desempenho de um motor multicombustível turboalimentado sem prejuízo à eficiência energética global - Jose Guilherme Coelho Baeta (2006)
The new trends of the automotive market require the development of a new concept of engines using different types of fuel, mainly those resulting from alternative sources of energy. Moreover, the multifuel engines available in the market display only one volumetric compression ratio, which leaves space for the development of systems that allow for different forms of combustion control according to the type of fuel used. This work aims at achieving the best performance for gasoline, alcohol and compressed natural gas vehicular, through the variation of the boost pressure in the multifuel turbocharged engine. The turbocharging aims at maximizing the torque without any reduction in the original engine efficiency . A turbocharger, a programmable Electronic Central Unit and a compressed natural gas vehicular multipoint injection system of 5thgeneration have been coupled to the engine. The depuration of in-cylinder pressure data supplied important parameters about the combustion process. The calibration variables and the engine control system maps were analyzed and compared for the different fuels and engine configurations. The turbocharging produced significant improvementscompared to the best versions of the naturally aspirated engine. The gasoline turbocharged engine has achieved a small gain in torque at Wide Open Throttle due to the volumetric compression ratio of 11:1 which is already a high compression ratio even for naturally aspirated engine. This reduced gain is caused by a drastic reduction of the ignition advance angle limited by the knock. The performance at partial throttle loadedoperation benefits from the high compression ratio used for the turbocharged engine. The combustion analysis shows almost the same flame propagation speed for alcohol and methane gas using the same volumetric compression ratio. Nevertheless the higher flame propagation speed for the gasoline is demonstrated by the in-cylinder pressuredata depuration obtained from the volumetric compression ratio of 12,5:1 using a blend of 50% of E25 and 50% of E94 in volume. The lowest mean turbulence factors for the turbocharged engine and the presence of residual burnt gases inside the chamber explain the lower flame propagation speed for this engine as compared to the naturally aspiratedversion. The turbocharged engine displayed the highest mean flame propagation speed with gasoline. It was followed by alcohol and then by the methane gas.